Educational Training For Processing Invoice Of Vendor Identification And Payments Using Python-Tesseract - et. al., Rekha M, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The aim of the project is to recognize the invoices of receipts from various vendors, by using automated invoice processing using various learning educational tools. This automated invoice processing is far better than manual invoice processing, it saves a serious amount of time and money creating efficiencies and increasing the accuracy of captured data. Basically, the invoices were calculated from the scanned receipts by using python-tesseract software. Python- tesseract is an optical character recognition (OCR) tool for python. It will recognize and read the text embedded in images. So, this python-tesseract software extracts key information like bill or invoice number, amount etc.; from all receipts and imports the calculated invoices and total amount of all receipts which are given by vendors to the database.